Effects of Alloying Elements on the Corrosion Behavior of Sputter–deposited Zr–(12–21)Cr–W Alloys in 0.5 M NaCl Solution - Aryal, Basu Ram; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2010)
The synergistic effect of the simultaneous additions of tungsten and zirconium in the sputter-deposited amorphous or nanocrystalline Zr-(12-21)Cr-W alloys is studied in 0.5 M NaCl solution open to air at 25°C using corrosion tests and open circuit potential measurements. Corrosion rates of the sputter-deposited Zr-(12-21)Cr-W alloys containing 10-80 at % tungsten (that is, 0.95-1.85 x 10-2 mm.y-1) are more than one order of magnitude lower than that of the sputter-deposited tungsten and even lower than those of zirconium as well as chromium in 0.5 M NaCl solution. The addition of 8-73 at % zirconium content in the sputter-deposited binary W-(12-21)Cr alloys seems to be more effective to improve the corrosion-resistant properties of the sputter-deposited ternary Zr-Cr-W alloys containing 12-21 at % chromium in 0.5 M NaCl solution. The sputter-deposited Zr-(17-21)Cr-W alloys containing an adequate amounts of zirconium metal showed the more stable passivity and showed higher corrosion resistance than those of alloy-constituting elements in 0.5 M NaCl solution open to air at 25°C. Keywords: Zr-(12-21)Cr-W alloys, sputter deposition, corrosion test, open circuit potential, 0.5 M NaCl. DOI: 10.3126/jncs.v25i0.3305 Journal of Nepal Chemical Society Volume 25, 2010 pp 75-82